2011
DOI: 10.1242/dev.065995
|View full text |Cite
|
Sign up to set email alerts
|

FGF/EGF signaling regulates the renewal of early nephron progenitors during embryonic development

Abstract: SUMMARYRecent studies indicate that nephron progenitor cells of the embryonic kidney are arranged in a series of compartments of an increasing state of differentiation. The earliest progenitor compartment, distinguished by expression of CITED1, possesses greater capacity for renewal and differentiation than later compartments. Signaling events governing progression of nephron progenitor cells through stages of increasing differentiation are poorly understood, and their elucidation will provide key insights int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 54 publications
5
99
2
2
Order By: Relevance
“…On the other hand, phosphatidylinositol 3-kinase (PI3K) and Akt, downstream signaling molecules of Ret, the kinase subunit of the glial cell line-derived neurotrophic factor (GDNF) receptor, promote branching morphogenesis (13). Recent evidence suggests a role of PI3K for the maintenance of progenitor cells as well (14). The multifunctional protein β-catenin mediates canonical Wnt signaling, and is necessary for both nephrogenesis and ureteric branching (15,16).…”
mentioning
confidence: 99%
“…On the other hand, phosphatidylinositol 3-kinase (PI3K) and Akt, downstream signaling molecules of Ret, the kinase subunit of the glial cell line-derived neurotrophic factor (GDNF) receptor, promote branching morphogenesis (13). Recent evidence suggests a role of PI3K for the maintenance of progenitor cells as well (14). The multifunctional protein β-catenin mediates canonical Wnt signaling, and is necessary for both nephrogenesis and ureteric branching (15,16).…”
mentioning
confidence: 99%
“…13,14 Subsequent analysis determined that only two Fgfs (2 and 9) that are expressed in the mouse ureteric bud at the time of induction are also sufficient to promote survival. 15 However, independently, neither of these genes is necessary for survival, suggesting that they may act redundantly. More recent studies have shown that Fgf20 is also sufficient for survival and it is necessary to maintain proper cell number.…”
Section: Survivalmentioning
confidence: 99%
“…19 Depending on the source and treatment of the isolated progenitors, Fgfs appear to only maintain survival of cells at a specific stage of differentiation. 15,20 More work will be required to tease out the specific roles of Fgfs during progenitor cell survival, proliferation, and differentiation.…”
Section: Survivalmentioning
confidence: 99%
“…Cette mutation ségrégeait avec l'agé-nésie rénale dans la famille. Des études montrant l'implication de la voie FGF dans le développement rénal [8,9], ainsi que l'expression de FGF20 au niveau du mésenchyme métanéphrique condensé dans le rein en développement (http:// www.gudmap.org/), suggéraient que cette mutation était bien responsable de l'agénésie rénale. Parallèlement, l'équipe de R. Kopan (Washington University, St Louis, États-Unis) avait généré une souris invalidée pour Fgf20 par insertion du gène de la -galactosidase (Gal) au niveau de l'exon 1.…”
Section: Le Développement Rénalunclassified
“…L'inactivation spécifique de Fgf9 dans le bourgeon urétéral ou dans le mésenchyme métanéphrique condensé a permis de montrer qu'une signalisation paracrine via Fgf9 coopère avec un signal autocrine produit par Fgf20 et Fgf9 dans le mésenchyme métanéphrique condensé, pour le maintien des cellules progéni-trices Six2 + [7] (Figure 1). L'implication des voies RAS et PI3K (phosphoinositide 3-kinase), en aval de la voie FGF, a par ailleurs été rapportée [9]. Enfin, des expériences de culture organotypique de métanéphros prélevés à E11,5 ont été réalisées en présence de protéines FGF recombinantes.…”
Section: Référencesunclassified